Metastable Brominated Nanodiamond Surface Enables Room Temperature and Catalysis-Free Amine Chemistry - Melendrez, Cynthia; Lopez-Rosas, Jorge A; Stokes, Camron X; Cheung, Tsz Ching; Lee, Sang-Jun; Titus, Charles James; Valenzuela, Jocelyn; Jeanpierre, Grace; Muhammad, Halim; Tran, Polo; Sandoval, Perla Jasmine; Supreme, Tyanna; et al. (The journal of physical chemistry letters, 2022)
Bromination of high-pressure, high-temperature (HPHT) nanodiamond (ND) surfaces has not been explored and can open new avenues for increased chemical reactivity and diamond lattice covalent bond formation. The large bond dissociation energy of the diamond lattice-oxygen bond is a challenge that prevents new bonds from forming, and most researchers simply use oxygen-terminated NDs (alcohols and acids) as reactive species. In this work, we transformed a tertiary-alcohol-rich ND surface to an amine surface with ∼50% surface coverage and was limited by the initial rate of bromination. We observed that alkyl bromide moieties are highly labile on HPHT NDs and are metastable as previously found using density functional theory. The strong leaving group properties of the alkyl bromide intermediate were found to form diamond-nitrogen bonds at room temperature and without catalysts. This robust pathway to activate a chemically inert ND surface broadens the modalities for surface termination, and the unique surface properties of brominated and aminated NDs are impactful to researchers for chemically tuning diamond for quantum sensing or biolabeling applications.